Conceptual bases of modeling of human language in computer systemsas a scientific base of information sciencesin higher school - Крехно, Т. І.; Мицюра, І. О. (Scientific notes of the pedagogical department, 2017)
The article is devoted to modeling of human language in computer systems. Modeling of human language in computer systems is treated as a scientific theoretical basis of information sciences in higher school.The formalization of speech and thought processes is treated as a prerequisite of intellectualization of computer technologies; formation of students' scientific foundations of linguistic computer simulation is presented as a necessary qualification characteristics of future specialists.